Subjective Well Being In Amaliah Manaqib’s Suryalaya Islamic Boarding School (Journal of Namibian Studies : History Politics Culture, 2024)
Humans always expect a comfortable and happy life. One of their efforts to achieve it is to seek spiritual peace. This effort is by participating in the Amaliah Manaqib event at the Suryalaya Islamic Boarding School. This research aims to analyze the types of Amaliah Manaqib's activities and SWB Ikhwan in the activities at the Islamic Boarding School Suryalaya. The method used in this research is a qualitative method with the type of phenomenological research. The results of this study indicate that Amaliah manaqib at the Suryalaya Islamic Boarding School is one of many that raises SWB for the Ikhwan. However, there are other dominant factors, such as routine remembrance of Jahar and khafi independently or in the congregation. The SWB concept at the Suryalaya Islamic Boarding School was found in the form of an evaluation system compiled by Abah Sepuh, and Abah Anom called Inabah.